Design, Synthesis, and Biological Evaluation of Novel 3, 5‐Disubstituted‐1, 2, 6‐Thiadiazine‐1, 1‐Dione Derivatives as HIV‐1 NNRTIs. (10th September 2013) - Tian, Ye; Rai, Diwakar; Zhan, Peng; Pannecouque, Christophe; Balzarini, Jan; De Clercq, Erik; Liu, Huiqing; Liu, Xinyong
Abstract : On the basis of structural features, binding mode, and structure–activity relationship studies of two pyrimidine‐derived non‐nucleoside reverse‐transcriptase inhibitors, DABOs, and diaryl pyrimidines, a novel class of 1, 2, 6‐thiadiazine‐1, 1‐dione derivatives were rationally designed using the strategies of bioisosterism and molecular hybridization, synthesized, and evaluated for their anti‐HIV activity in MT4 cell cultures. Three compounds were found to have moderate activity against HIV‐1 replication with EC50 values ranging from 23 to 32 μm . To further confirm the binding target, compoundIIg was selected to conduct an HIV‐1 reverse‐transcriptase inhibitory assay. In addition, preliminary structure–activity relationship analysis among the newly synthesized compounds was discussed, and the binding mode of the active compoundIIg was rationalized by molecular docking and physicochemical studies. Abstract : On the basis of studies of two pyrimidine‐derived non‐nucleoside reverse‐transcriptase inhibitors, DABOs, and diaryl pyrimidines, a novel class of 1, 2, 6‐thiadiazine‐1, 1‐dione derivatives were rationally designed using the strategies of bioisosterism and molecular hybridization, synthesized, and evaluated for their anti‐HIV activity in MT4 cell cultures. Three compounds were found to have moderate activity against HIV‐1 replication with EC50 values ranging from 23 to 32 μm . In addition, HIV‐1 RT inhibitory assay, preliminary structure–activity relationship analysis, molecular docking studies were proformed.